2022
DOI: 10.1039/d1cp05689a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-nanocluster science and technology: my personal history and outlook

Yuichi Negishi

Abstract: Metal nanoclusters (NCs) are among the leading targets in research of nanoscale materials, and elucidation of their properties (science) and development of control techniques (technology) have been continuously studied for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 327 publications
(546 reference statements)
1
22
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14] Such species are desirable in devices for applications in energy, catalysis, biomedicine, and environment, among others, 9,[15][16][17][18][19][20][21][22][23][24] providing the ability to achieve tailorable species. [25][26][27][28][29][30][31][32][33][34] Both experimental and theoretical efforts 4,30,[35][36][37][38][39][40][41][42] have enabled further elucidation of the inherent properties of ultrasmall nanoparticles, [43][44][45] leading to the understanding of both the structural and electronic features, usually rationalized via the divide-and-protect approach. 20,46 In this regard, [Au 25 (SR) 18 ] (R = ligand) is one of the most prototypical and recurrent ligand-protected gold clusters...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14] Such species are desirable in devices for applications in energy, catalysis, biomedicine, and environment, among others, 9,[15][16][17][18][19][20][21][22][23][24] providing the ability to achieve tailorable species. [25][26][27][28][29][30][31][32][33][34] Both experimental and theoretical efforts 4,30,[35][36][37][38][39][40][41][42] have enabled further elucidation of the inherent properties of ultrasmall nanoparticles, [43][44][45] leading to the understanding of both the structural and electronic features, usually rationalized via the divide-and-protect approach. 20,46 In this regard, [Au 25 (SR) 18 ] (R = ligand) is one of the most prototypical and recurrent ligand-protected gold clusters...…”
Section: Introductionmentioning
confidence: 99%
“…5–14 Such species are desirable in devices for applications in energy, catalysis, biomedicine, and environment, among others, 9,15–24 providing the ability to achieve tailorable species. 25–34 Both experimental and theoretical efforts 4,30,35–42 have enabled further elucidation of the inherent properties of ultrasmall nanoparticles, 43–45 leading to the understanding of both the structural and electronic features, usually rationalized via the divide-and-protect approach. 20,46…”
Section: Introductionmentioning
confidence: 99%
“…18−22 There are several examples where LEIST brings forth opportunities in functionalizing and tailoring the surface structure via understanding the gradual structural change in the parent NCs when treated at high temperature with excess free ligands. 23−25 For example, an extensive ligand exchange on Au 25 (SR) 18 NC with different thiolate ligands showed that Au 25 could accommodate a wide variety of thiolate ligands. 26−29 Ligand exchange performed on the Au 25 (SG) 18 (SG = glutathione) NC with functionalized glutathione also revealed modulated optical properties of Au 25 (SG) 18 .…”
mentioning
confidence: 99%
“…23−25 For example, an extensive ligand exchange on Au 25 (SR) 18 NC with different thiolate ligands showed that Au 25 could accommodate a wide variety of thiolate ligands. 26−29 Ligand exchange performed on the Au 25 (SG) 18 (SG = glutathione) NC with functionalized glutathione also revealed modulated optical properties of Au 25 (SG) 18 . 30 The observation of enhancement in stability of Au 25 (SR) 18 NC upon ligand exchange with selenolate ligand underlies the importance of LEIST in obtaining desired properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation